Controlling all degrees of freedom of the optical Coupling in hybrid quantum photonics - Lettner, Niklas; Antoniuk, Lukas; Ovvyan, Anna; Gehring, Helge; Wendland, Daniel; Agafonov, Viatcheslav N.; Pernice, Wolfram; Kubanek, Alexander (ACS photonics, 2024)
Nanophotonic quantum devices can significantly boost light-matter interaction, which is important for applications such as quantum networks. Reaching a high interaction strength between an optical transition of a spin system and a single mode of light is an essential step that demands precise control over all degrees of freedom of the optical coupling. While current devices have reached a high accuracy of emitter positioning, the placement process remains overall statistically, reducing the device fabrication yield. Furthermore, not all degrees of freedom of the optical coupling can be controlled, limiting the device performance. Here, we develop a hybrid approach based on negatively charged silicon vacancy center in nanodiamonds coupled to a mode of a Si3N4-photonic crystal cavity, where all terms of the coupling strength can be controlled individually. We used the frequency of coherent Rabi oscillations and line-broadening as a measure of the device performance. This allows for iterative optimization of the position and rotation of the dipole with respect to individual preselected modes of light. Therefore, our work marks an important step for optimization of hybrid quantum photonics and enables us to align device simulations with real device performance.
Gesehen am 19.08.2024